The goals of the sustainable tourism development and management in the Fruška Gora National park - Trišić Igor (Turističko Poslovanje, 2018)
This paper presents the results of research of a significant number of activities with analysis, aimed at preventing the negative impact of tourism in the area of National park 'Fruška gora', in which tourism activities take place. Consideration of the existing situation and models of area protection, can have positive results through contributions to future planning strategies for the protection of this area and improvement of tourism development. The aim is to constitute new or implement existing protection measures with proper monitoring, for the purpose of achieving positive ecological and social results of the long-term character.